Diversidade genética de uma população isolada de bugio-ruivo (Alouatta guariba clamitans) (Cabrera 1940) no Parque Estadual das Fontes do Ipiranga, São Paulo – SP - Monticelli, Cauê (Universidade Federal de São Carlos, 2019)
The fragmentation of the habitat mainly through anthropic causes may infer the genetic variability of species, specially over isolated populations in small fragments, leading to the reduction in population size, and spreading potential. Parque Estadual das Fontes do Ipiranga (PEFI) is the largest fragment of Atlantic Forest inserted in the Metropolitan Region of São Paulo. For being an isolated area in urban environment, it takes the insular effect and it is under anthropogenic pressure that generates negative impact to the local biodiversity. Within wild species, the red howler monkeys (Alouatta guariba clamitans) is the only autochthone primate. Starting from the hypothesis that the isolated population of red howlers of PEFI is endogamic and it presents low genetic diversity, 10 loci heterological microsatellite indicators have been used in order to assess the genetic diversity, endogamy coefficient, population bottleneck, and initial information over the population structure, and familyhood. Thus, the DNA extraction and genotyping of the blood samples were performed in 30 animals captured. As a result, 49 alleles were found with an average of 4,9 alleles per loco, being 2,95 the effective number of alleles, a richness allelic average of 4,73, average Ho of 0,49, and average He = 0,58. It was observed a deficit in heterozygotes and Fis endogamic coefficient being 0,16, pointing the occurrence of inbreeding. The Pearson correlation test and the analysis of variance (ANOVA) were used in order to analyze the relation between the geographic distance of the captured animals and the genetic distance obtained through the analysis of familyhood and, based on the results obtained, it has been observed a greater proximity of male adults family-related than non-related male adults. The populational reduction test has not detected recent population bottlenecks. Nevertheless, in spite of the absence of bottlenecks and the moderate genetic diversity found, the population of brown howlers of PEFI has presented a considerable average of endogamic coefficient, and genetic diversity inferior to other isolated populations.
Genetic diversity of an isolated population of red howler monkeys (Alouatta guariba clamitans) (Cabrera 1940) in the State Park of Fontes do Ipiranga, São Paulo - SP
Keywords: Microssatélite; Parentesco; Estrutura populacional; PEFI; Atelidae; Microsatellite; Kinship; Population structure; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL